Iron regulation of transferrin receptor mRNA levels requires iron-responsive elements and a rapid turnover determinant in the 3' untranslated region of the mRNA. - Casey, J L (1989)
Post-transcriptional regulation of transferrin receptor mRNA levels by iron is mediated by a portion of the 3' untranslated region (UTR) of the mRNA. We have previously shown that a 678 nucleotide fragment of the 3'UTR contains the regulatory element(s). Within this region are five RNA structures which resemble the iron-responsive element (IRE) in the 5' untranslated region of the ferritin mRNA which is regulated translationally by iron. The IREs from the ferritin and transferrin receptor mRNAs compete in an in vitro assay for interaction with a cytoplasmic protein; the activity of this IRE-binding protein is dependent upon the iron status of the cells. Based on further deletion analysis reported here, the sequence required for iron regulation of the transferrin receptor have been limited to 250 nucleotides which we have produced synthetically and cloned. This sequence, which contains three IREs, is capable of producing iron-dependent regulation of transferrin receptor levels. Removal of the three IREs from the synthetic element results in loss of iron regulation. Moreover, deletion of a single cytosine residue from each of the three IREs in the synthetic regulatory element eliminates high-affinity binding to the IRE-binding protein in vitro and results in low levels of iron-independent transferrin receptor expression, consistent with production of a constitutively unstable mRNA. These data indicate that the ability of the mRNA to interact with the IRE-binding protein is required for regulation of transferrin receptor mRNA levels by iron.(ABSTRACT TRUNCATED AT 250 WORDS)